RAISING FUNDS FROM INTERNATIONAL FINANCIAL INSTITUTIONS (Proceedings of International Educators Conference, 2024)
The article examines the role of attracted funds from international financial institutions in providing loans to investment projects of corporate clients of commercial banks. The foreign experience of attracting and placing borrowed funds, the role of reforming the banking system of the Republic of Uzbekistan in improving the mechanisms of work with international financial institutions has been studied. The analysis of the attracted funds of a commercial bank is given.